FRAUD PENTAGON DAN KECURANGAN LAPORAN KEUANGAN - Sekar Akrom Faradiza (Fakultas Ekonomi dan Bisnis Islam, UIN Sunan Kalijaga Yogyakarta, 2018)
Nowadays fraudulent actions on financial statements are increasing. The impact of these actions is not only felt by investors individually but also affects global economic stability. There has been a lot of research related to fraud using fraud triangle model consists of pressure, opportunity and rationalization. Then fraud diamond model emerged that added capability as one of the factors related to fraud as an additional factor besides three factors on the fraud triangle model. Then fraud pentagon model appeared which also included arrogance factors related to fraud. This study aims to examined the influence of factors on fraud pentagon model (arrogance, competence / capability, pressure, opportunity and rationalization) on fraudulent financial statements. This research used manufacturing company listed in Indonesia Stock Exchange as samples and used data from 2014-2015. Data were analyzed using multiple linear regression. The results indicate that arrogance does not affect fraudulent financial statements.